Early Surgical Repair of Bile Duct Injuries following Laparoscopic Cholecystectomy: The Sooner the Better - Battal, Muharrem; Yazici, Pinar; Bostanci, Ozgur; Karatepe, Oguzhan (The Surgery Journal, 2019)
Background We aimed to investigate the outcomes of the immediate surgical repair of bile duct injuries (BDIs) following laparoscopic cholecystectomy.Materials and Methods Between January 2012 and May 2017, patients, who underwent immediate surgical repair (within 72 hours) for postcholecystectomy BDI, by the same surgical team expert in hepatobiliary surgery, were enrolled into the study. Data collection included demographics, type of BDI according to the Strasberg classification, time to diagnosis, surgical procedures, and outcome.Results There were 13 patients with a mean age of 43 ± 12 years. Classification of BDIs were as follows: type E in six patients (46%), type D in three patients (23%), type C in two (15%), and types B and A in one patient each (7.6%). Mean time to diagnosis was 22 ± 15 hours. Surgical procedures included Roux-en-Y hepaticojejunostomy for all six patients with type-E injury, primary repair of common bile duct for three patients with type-D injury, and primary suturing of the fistula orifice was performed in two cases with type-C injury. Other two patients with type-B and -A injury underwent removal of clips which were placed on common bile duct during index operation and replacing of clips on cystic duct where stump bile leakage was observed probably due to dislodging of clips, respectively. Mean hospital stay was 6.6 ± 3 days. Morbidity with a rate of 30% (n = 4) was observed during a median follow-up period of 35 months (range: 6–56 months). Mortality was nil.Conclusion Immediate surgical repair of postcholecystectomy BDIs in selected patients leads to promising outcome.
Keywords: cholelithiasis; laparoscopic cholecystectomy; hepato-pancreato-biliary surgery; postoperative complication; bile duct injury; emergency surgery; surgical repair